Austroeupatorium inulifoliumnvasion alters soil microbial populations to facilitate its own growth - Iresha Karunaratne; Sumedha Madawala (Ceylon Journal of Science, 2016)
It is a known fact that invasive plants perform better in their introduced range than in the native range.  The invasion-driven modifications of the soil microbial community and alleolopathic compounds are considered as factors contributing to their success over co-occurring natives.  Here we present evidence to show that Austroeupatorium inulifolium invasion has altered the soil microbial population to facilitate its own growth.  A pot experiment showed higher growth increments in Austroeupatorium when grown in soil with a history of Austroeupatorium invasion compared to that with no history of invasion.  The native, Psiadia ceylanica showed no parallel growth increments when grown under similar conditions.  In support, the enzyme activities (catalase and dehydrogenase) and soil microbial biomass carbon also recorded higher values in invaded soils compared to un-invaded soils. Further, Austroeupatorium showed higher dependence on arbuscular mycorrhizal fungi (AMF) than that of the native, Psiadia.  The results suggest that Austroeupatorium invasion has enhanced soil microbial populations and functions in order to take the advantage over other natives.